Spectrum of BRCA1/2 point mutations and genomic rearrangements in high-risk breast/ovarian cancer Chilean families - Gonzalez-Hormazabal, Patricio; Gutierrez-Enriquez, Sara; Gaete, Daniel; Reyes, Jose M.; Peralta, Octavio; Waugh, Enrique; Gomez, Fernando; Margarit, Sonia; Bravo, Teresa; Blanco, Rafael; Diez, Orland; Jara, Lilian (Breast cancer research and treatment, 2011)
The distribution of BRCA1/2 germline mutations in breast/ovarian cancer (BC/OC) families varies among different populations. In the Chilean population, there are only two reports of mutation analysis of BRCA1/2 , and these included a low number of BC and/or OC patients. Moreover, the prevalence of BRCA1/2 genomic rearrangements in Chilean and in other South American populations is unknown. In this article, we present the mutation-detection data corresponding to a set of 326 high-risk families analyzed by conformation-sensitive gel electrophoresis and heteroduplex analysis. To determine the contribution of BRCA1/2 LGRs in Chilean BC patients, we analyzed 56 high-risk subjects with no pathogenic BRCA1/2 point mutations. Germline BRCA1 / 2 point mutations were found in 23 (7.1%) of the 326 Chilean families. Families which had at least three BC and/or OC cases showed the highest frequency of mutations (15.9%). We identified 14 point pathogenic mutations. Three recurrent mutations in BRCA1 (c.187_188delAG, c.2605_2606delTT, and c.3450_3453delCAAG) and three in BRCA2 (c.4969_4970insTG, c.5374_5377delTATG, and c.6503_6504delTT) contributed to 63.6 and 66.7% of all the deleterious mutations of each gene, which may reflect the presence of region-specific founder effects. Taken together BRCA1/2 recurrent point mutations account for 65.2% (15/23) of the BRCA1/2 (+) families. No large deletions or duplications involving BRCA1 / 2 were identified in a subgroup of 56 index cases negative for BRCA1/2 point mutations. Our study, which is the largest conducted to date in a South American population, provides a comprehensive analysis on the type and distribution of BRCA1/2 mutations and allelic variants.